Structure and hardness of in situ synthesized nano-oxide strengthened CoCrFeNi high entropy alloy thin films. (October 2021) - Lee, Subin; Chatain, Dominique; Liebscher, Christian H.; Dehm, Gerhard
Graphical abstract: Abstract: In this study, we report on face-centered cubic structured CoCrFeNi high-entropy alloy thin films with finely dispersed nano-oxide particles which are formed by internal oxidation. Analytical scanning transmission electron microscopy imaging found that the particles are Cr 2 O 3 . The oxide particles contribute to the hardening of the film increasing its hardness by 14% compared to that of the film without precipitates, through the Orowan-type strengthening mechanism. Our novel approach paves the way to design medium- and high-entropy alloys with high strength by making use of oxide phases.